A Rare Case of Adrenal Metastasis Diagnosed before Discovery of Invasive Ductal Breast Cancer which was Confirmed to Be the Primary Site - Kamido, Satoshi (Hinyokika kiyo. Acta urologica Japonica, 2022)
A 54-year-old female underwent open left adrenalectomy for a left adrenal tumor in 2013. The pathology showed metastatic poorly differentiated adenocarcinoma. Despite a close examination, the primary tumor could not be identified. During the follow-up, a computed tomographic scan showed a hyper vascular tumor in the left breast in2015. A left mastectomy was performed for diagnosis and treatment. The pathology showed invasive ductal carcinoma of the breast. Comparing the histopathology and immunohistochemistry of the breast tumor with the adrenal tumor, the adrenal tumor was finally confirmed as metastatic invasive ductal carcinoma. Adrenal gland metastasis from invasive ductal carcinoma is said to be extremely rare. To our knowledge, there have been no reports of cases in which metastatic invasive ductal carcinoma of the adrenal gland was found before the primary site. We report this case with some literature review